Geochemical Characteristics of Strongly Acidic Thermal Water of the Tamagawa Hot Spring in North-Eastern Japan û Implications for Source and Transportation of Rare Metals in Magmatic Hydrothermal to Geothermal Systems - D Ishiyama; T Mizuta; T Nakano (The Australasian Institute of Mining and Metallurgy, 2008)
The Tamagawa Hot Spring, from which Ra-Pb-Sr-bearing barite precipitates, is a representative hot spring in a volcanic gas-bearing hydrothermal system associated with Quaternary andesitic to dacitic magmatic activity beneath the Yakeyama Volcano. Thermal water in the Tamagawa Hot Spring is divided into three types: Cl-SO4-type (Ohbuki hot spring: pH 1.2); SO4-type (pH 1.8 to 2.9); and neutral-type (pH 6.1). The concentrations of dissolved components in the Ohbuki Cl-SO4-type thermal water are about ten times higher than in the SO4-type thermal water. The 87Sr/86Sr isotopic signatures of the Ohbuki Cl-SO4-type thermal waters (0.703992 ¦ 0.000004 to 0.704032 ¦ 0.000006) are different from those of SO4-type thermal waters (0.704245 ¦ 0.000003) formed by the interaction of andesitic volcanic rocks (0.704065 ¦ 0.000007 to 0.704093 ¦ 0.000009) and groundwater derived from river water (0.704314 ¦ 0.000012 to 0.704519 ¦ 0.000013) in a shallower part of the hot spring area. The possible origins of Sr in the Ohbuki Cl-SO4-type thermal water and in the SO4-type thermal water are different. The Sr isotopic ratios (0.704130 ¦ 0.000012 to 0.707556 ¦ 0.000014) of Aniai Formation andPreYakeyama Lake deposits occurring below the hot spring area are distinctly higher than those of the Cl-SO4-type thermal water. However, it is expected that a solidifying andesitic or dacitic magma which has similar Sr isotopic ratios of the Ohbuki Cl-SO4-type thermal water, occur in the deep portion of the Tamagawa Hot Spring. The Cl-SO4-type thermal waters having low Sr isotopic ratios do not acquire their Sr isotopic signatures by interaction with strata below the hot spring area, but they are likely to reflect water interaction with a solidifying magma with low Sr isotopic ratios. Components including rare metals in Cl-SO4 type thermal water could be transported from a deeper part. An EXTENDED ABSTRACT is available for download. A full-length paper was not prepared for this presentation.